COMPONENT-LEVEL ANALYSIS OF QUANTITY TAKE-OFF DEVIATIONS BETWEEN BIM AND CONVENTIONAL METHODS IN REINFORCED CONCRETE BRIDGE STRUCTURES - Indra Kusuma; Dedi Enda (RADJA PUBLIKA, 2026)
Material quantity calculation is a critical stage in construction planning because the accuracy of quantity estimation directly affects project cost control and decision-making. In bridge construction, Quantity Take-Off (QTO) is commonly performed using conventional methods based on two-dimensional drawings, which may lead to quantity deviations due to geometric simplifications and limitations in representing complex structural details. This study aims to compare concrete and reinforcement quantities obtained using conventional methods and Building Information Modeling (BIM) through Autodesk Revit, as well as to identify the factors causing quantity deviations in bridge components. The research was conducted on the Tanjung Alai Village Bridge by developing a three-dimensional BIM model based on Detail Engineering Design (DED) drawings. Quantity comparisons were evaluated using percentage error and Root Mean Square Error (RMSE) analyses. The results showed average error values of 0.157% for concrete and 1.559% for reinforcement, with RMSE values of 0.015 m³ and 0.009 m³, respectively. The largest concrete deviation occurred in the Backwall due to its non-prismatic geometry, while the largest reinforcement deviation was found in the wing wall because BIM captured actual reinforcement length variations not fully represented in conventional calculations. These findings indicate that BIM provides reliable quantity estimation and a more detailed representation of structural geometry and reinforcement configurations in reinforced concrete bridge structures